COVID-19 Preventative Measures: Cloth Face Coverings for Food Employees - Michelle D. Danyluk; Natalie Seymour; Mary Yavelak; Candice Christian; Ben Chapman (EDIS)
This one-page full-color handout depicts essential components of a cloth face covering for use in food settings and provides information on the following topics: